Differences in Musculoskeletal Disorder Risk Levels between Students who attend Offline and Hybrid Lectures - Sarda Ika Devi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Lectures by sitting for a long time without doing physical activity and resting can have an impact on musculoskeletal health in students. Purpose: This research is expected to be able to find out the difference in the risk level of Musculoskeletal Disorder between students who attend offline and hybrid lectures. Methods: This study used a cross-sectional study design with a total sample of 81 students, 52 samples are the offline student group and 29 samples are the hybrid students group, using the chi-square statistical test analysis. Results: Based on the Pearson chi-square statistical test, it can be seen that there is no difference in the risk level of musculoskeletal disorders in students attending hybrid and offline lecture methods, or it can be said that they have relatively the same risk level of MSDs (p=0.243) <α = 0.05